Knowledge, Health Seeking Behaviour on Febrile Conditions and Management Practices among Mothers of Under-Five Children in Selected Facilities in Ibadan, Nigeria (2022)
Background: Fever is the most common symptom of childhood illnesses and parents have been said to develop what is called “fever phobia” because of fear of death of their child. Due to this, parents’ resort to various practices to manage fever which is also a function of the parents’ knowledge about fever. Objectives: This study investigated the knowledge, health seeking behaviour, and management practices of fever among mothers of under-five children. Methodology: A cross-sectional descriptive design was used with a multistage technique to select 122 mothers from the Ibadan North and Akinyele Local government area of Oyo state. A self-developed instrument was used for data collection. Data were analysed and presented in frequency and percentages. Association between variables were tested using fisher’s test, p value was set at 0.05. Results: The mean age of the respondents was 30 years. Majority (75.5%) of mothers had good knowledge about fever in children. A majority (91.6 %%) stated that fever is a serious illness. More than half agreed that dehydration and discomfort (74.5%), convulsion and brain damage (83.4%) are negative outcomes of fever. Most (72.9%) of the mothers took their children to a health facility on account of fever. Majority (79%) gave drugs to manage fever in a child. Other methods used to manage fever include bathing the child (46.3%), tepid sponging the child (50.5%), prayer (43.8%), ventilation (37.7%), and a sprinkling of anointing oil (19.7%). Conclusion: Findings from the study showed that mothers have good knowledge of fever. However, there is a gap in management. In the light of this, it will be imperative for nurses and midwives to educate mothers using on the management and prevention of fever in children.